Update and new advances in fertility preservation and cancer - Gwendolyn P. Quinn; Michelle Bayefsky; Brooke Cherven; Lauren V. Ghazal; Kara N. Goldman; Nina Francis Levin; Leena Nahata; Bobby Najari; Sameer Thakker; Daniel R. Greenberg; Joshua A. Halpern; Susan T. Vadaparampil (CA: A Cancer Journal for Clinicians, 2025)
Abstract Adolescents and young adults with a cancer diagnosis face unique challenges during treatment and into survivorship related to fertility and family building. This review provides an updated overview of the impact of cancer and its associated treatments, including novel treatments in male and female fertility. An overview of fertility preservation and family building options, including experimental options, is also provided.